KEARIFAN LOKAL MASYARAKAT DALAM MENJAGA KELESTARIAN HUTAN ADAT TAWANG PANYAI DI DESA TAPANG SEMADAK KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Juniarti, Selly Rismi; Iskandar AM, .; Yani, Ahmad (Universitas Tanjungpura, 2016)
The Tawang Panyai Customary Forest has various species of trees which produce timber, fruits, medicinal plants, rattan and bamboo used by the indigenous De’sa Dayak people around it. To date, the Tawang Panyai Customary Forest is well preserved through local wisdom of the local community. This research aims to find out the forms of local wisdom and describe how such wisdom in the community preserve the Tawang Panyai Customary Forest in the village of Tapang Semadak in Subdistrict of Sekadau Hilir, Sekadau Regency. The research findings show that there are six forms of local wisdom in preserving the forest i.e. prohibition on felling / stealing trees in the forest, prohibition on taking or killing animals, prohibition on opening the customary forest for farming, myth/belief about bunyik (ghost), traditional rituals of badarak, maintaining good attitude and speech. Keywords: Local Wisdom, Community, Preservation of Tawang Panyai Customary Forest.